Autoimmune Encephalitis: Pathophysiology, Diagnosis and Treatment - Coalter, Matthew; Dunne, Jean (Trinity Student Medical Journal, 2018)
Autoimmune encephalitis is a family of similar neuropsychiatric diseases presenting with a range of symptoms including subacute dysfunction in memory, decreased cognition, psychosis, refractory seizures, and encephalomyelopathy. During the initial investigation, infectious and medical causes of encephalitis must be ruled out and autoimmune aetiologies explored. Patients will often have a characteristic clinical history and findings, CSF pleocytosis, MRI T2-FLAIR, especially in temporal lobes and limbic system, and EEG changes. Specific autoantibodies can be detected using commercial laboratory tests with high sensitivity and specificity. The diseases can largely be broken down into group I encephalitides with autoantibodies against intracellular synaptic proteins, and group II encephalitides with autoantibodies against neuronal surface proteins. When a diagnosis is suspected, patients should receive first-line steroids and IVIG. If this fails, second-line immunotherapies rituximab and cyclophosphamide are recommended. The majority of autoimmune encephalitides have an association with various tumours and are therefore paraneoplastic syndromes in many patients. Comprehensive screening for cancer should be carried out in all patients, focusing on the specific cancer association, and appropriate cancer treatment can help ease neurological symptoms. Outcomes vary by disease and recovery is usually slow. This is a relatively newly recognised disease and new research is vital to increase recognition and form treatment strategies to best deal with this underdiagnosed condition. This is a review of the literature on the pathophysiology, diagnosis and treatment of autoimmune encephalitis.